Disseminated cryptococcosis in HIV negative patient. (12th May 2018) - Hassoun, Ali; Mehrotra, Neha
Abstract : A 52-year-old white diabetic male with 4-weeks history of persistent cough followed by headache, drenching night sweats, low-grade fever, worsening photophobia, nausea and vomiting was presented. Examination was significant for photophobia and diminution of vision. His spinal fluid and blood cultures were positive for Cryptococcus neoformans . Intravenous fluconazole were given for 2 weeks followed by oral fluconazole. There was significant improvement in systemic and ocular symptoms. HIV serology was negative, but his CD4 counts were low with inverted CD4:CD8 ratio.